2019
DOI: 10.1111/fare.12391
|View full text |Cite
|
Sign up to set email alerts
|

Adopted Children's Social Competence: The Interplay Between Past and Present Influences

Abstract: Objective To explore potential postadoption moderators of the link between preadoption experiences and adoptees' social competence. Background In the context of the limited and inconsistent knowledge about adopted children's social competence, our hypotheses concern the interplay between preadoption parental neglect and adoptive parents' emotion socialization practices. Method With adopters as informants, the social competence of 97 Portuguese school‐age children was evaluated in terms of social skills and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…Children who have a deficit in their social skills will experience barriers to their emotional development. He tends to have difficulty communicating with his peers, teachers, and family (Soares et al, 2019). In addition, being unskilled in social use is shown by a negative relationship with behavioral adjustment skills (Hygen et al, 2020).…”
Section: Social Competencementioning
confidence: 99%
“…Children who have a deficit in their social skills will experience barriers to their emotional development. He tends to have difficulty communicating with his peers, teachers, and family (Soares et al, 2019). In addition, being unskilled in social use is shown by a negative relationship with behavioral adjustment skills (Hygen et al, 2020).…”
Section: Social Competencementioning
confidence: 99%
“…When infancy is marked by maltreatment, neglect and/or experience of collective/group care (institutionalization), as it is the case for most adopted children, the overall development and, particularly, the socioemotional one, are heavily damaged by the lack of an individualized, responsive, supportive, and stable/permanent care. Research has shown that early adversity experiences affect social competence, specifically the acquisition and performance of social skills (e.g., Cáceres et al, 2021;Julian & McCall, 2016;Pitula et al, 2019;Soares et al, 2019).…”
Section: Adopted Children's Social Skillsmentioning
confidence: 99%
“…Recent adoption research has shown that most adoptees present adequate social functioning (e.g., DeLuca et al, 2018), significantly better than children in institutions (e.g., Barroso et al, 2018;Cáceres et al, 2021;Palacios et al, 2013) despite the heterogeneity observed within the adopted-group, with a subgroup of adoptees poorly competent, with less social skills and/or rejected or neglected by peers (Barbosa-Ducharne, 2021). Children with higher exposition to early adversity showed fewer social skills (e.g., Julian & McCall, 2016;Soares et al, 2019), especially when adopted at an older age or from Eastern Europe (e.g., Barcons et al, 2012;Caprin et al, 2017). Recent research has also shown the positive influence of postadoption parenting/family dynamics on adoptees' social skills, as well as the effect of the interplay between past adversity and postadoption experiences on adoptees' social outcomes (e.g., DePasquale et al, 2020;Leve, Griffin et al, 2019;Soares et al, 2019).…”
Section: Parenting Temperament and Social Skills In Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under Portuguese legislation, residential care is one of the measures for the support and protection of children and young people at risk. Despite its negative impact on children’s development, residential care offers an ecological approach to clearly understand the effects of institutionalization on children’s developmental outcomes (Soares et al, 2019). The main legal reason for being removed from biological family and moving to residential care is negligence (71.7%), followed by other situations, such as temporary lack of family support, child disruptive behaviours, and abandonment by the biological family (12.3%), psychological maltreatment (9.6%), physical abuse (3.8%), and sexual abuse (2.6%) (Instituto da Segurança Social, 2018).…”
Section: Introductionmentioning
confidence: 99%